2013
DOI: 10.1093/rheumatology/ket405
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic examination of rheumatoid arthritis patients who are free of physical synovitis: power Doppler subclinical synovitis is associated with bone erosion

Abstract: PD subclinical synovitis correlates with several clinical characteristics, whereas conventional serum biomarkers are not useful for indicating the presence of subclinical PD synovitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 37 publications
4
28
0
4
Order By: Relevance
“…This confirms the general view that active synovitis revealed in PD is correlated with systemic inflammation [21,26]. Both Scirè et al [21] and Kawashiri et al [24] did not find any correlation between ESR values and the intensity of changes in power Doppler, which is also confirmed by us. A study by Xiao et al [19] revealed the presence of a correlation between CRP, ESR, and ACPA with the intensity of synovial thickening (GS).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This confirms the general view that active synovitis revealed in PD is correlated with systemic inflammation [21,26]. Both Scirè et al [21] and Kawashiri et al [24] did not find any correlation between ESR values and the intensity of changes in power Doppler, which is also confirmed by us. A study by Xiao et al [19] revealed the presence of a correlation between CRP, ESR, and ACPA with the intensity of synovial thickening (GS).…”
Section: Discussionsupporting
confidence: 89%
“…This should be taken into consideration when making decisions concerning the use of DMARDs. According to the data from literature, PD signal was present even in patients in clinical remission, which is a predictor of fast radiological damage progression in the involved joints [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…[21] были изуче-ны особенности субклинического синовита по данным ЭД у больных РА с клинической ремиссией. В исследование были включены 29 пациентов с РА.…”
Section: таблицаunclassified
“…При этом кор-реляции между УЗ-признаками синовита и концентрацией провоспалительных цитокинов (ФНОα, ИЛ6, ИЛ8, ИЛ17A, ИЛ17F, ИЛ18, ИЛ20, ИЛ23 и ИЛ33) также не отме-чено. В другом исследовании [21] у 29 пациентов с РА в клинической ремиссии на фоне успешной терапии была обнаружена связь персистирующего субклинического вос-Ф о р у м м о л о д ы х у ч е н ы х паления с наличием эрозий, однако при этом уровень био-маркеров (MMП3, СЭФР, ANG-2 и sRANKL) в группах с изменениями разной степени интенсивности, выявлен-ными по данным ЭД, не различался. Противоречивость результатов обусловлена тем, что большинство цитокинов в разные периоды времени могут оказывать стимулирующее или ингибирующее влияние на продукцию других цитокинов.…”
unclassified
“…Likewise, the degree of the PD signal at baseline is a predictor for radiologic progression in early RA [22,36,65,79,85,86] as well as in longstanding RA [52,69,[87][88][89][90]. In this respect, subclinical active synovitis could be considered a surrogate marker to define the disease activity or a complete remission status in treated RA patients [18,79,[91][92][93].…”
Section: Clinical Remission Versus Imaging Remissionmentioning
confidence: 99%